(untitled) (Indian Journal of Nematology, 2024)
Comparative quantification on four biochemical factors reveal that under moisture stress at 97% RH when IJ enter into partial anhydrobiosis, there was an increase in the accumulation of total sugar (3.0%) and non-reducing sugar (171.9%) while decrease in the levels of reducing sugar (25%) and total soluble proteins (52.8%), in comparison to fresh nematodes. There was no detrimental effect on the Photorhabdus due to anhydrobiotic stress on the IJ as the bacterial symbiont could be isolated on nutrient agar plates in phase I form. The bacteria retained their virulence by imparting 100% mortality in Galleria mellonella larvae when injected. Anhydrobiotic H. indica IJ aggregated to form large clumps but remained straight and did not coil.